Book Reviews (The Muslim world, 1991)
Book reviewed in this article: Sexuality and War: Literary Masks of the Middle East. By Evelyne Accad Islamic Reform: Politics and Social Change in Late Ottoman Syria. By David Dean Commins Khomeini's Forgotten Sons: The Story of Iran's Boy Soldters. By Ian Brown Bibliographical Guide to Iran: The Middle East Library Committee Guide. Edited by L. P. Elwell-Sutton